ANALISIS GEOMORFOLOGI KAWASAN KAMPUS LAPANGAN PPSDM GEOMINERBA DAN SEKITARNYA - Suryo Hespiantoro; Aperta Ledy Alam (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2019)
The PPSDM Geominerba Field Campus, is located in Gunung Masigit Village, Citatah Subdistrict, West Bandung Regency, West Java Province. The Campus lies on dominantly carbonate rocks area and cropout volcanic rocks at some other locations, that are formed different morphologies. The rocks composition and rocks physics are involving to constructed the morphology in this area. Based on the slope condition, landscape, and rocks composition, the landscape on PPSDM Geominerba Field Campus and it surrounding, divided into 2 (two) Geomorphology Units. First, Karst Morphology Unit (K2), 70% - 140% slope percent, very steep to almost vertical slope, and the area is constructed by dominantly coral limestone, and a littie bit of massive and crystalline limestones. Second, Denudational Geomorphology Unit (D2), 15% - 30% slope percent, moderately steep slope and the area is constructed by breccias and sandstone volcanic rocks, that reserved ground water or as aquifer layers in PPSDM Geominerba Field Campus and it surrounding. The result of this geomorphology study can be used for environment and geological hazards training materials.